2018
DOI: 10.7759/cureus.3195
|View full text |Cite
|
Sign up to set email alerts
|

Primary Causes of Hospitalizations and Procedures, Predictors of In-hospital Mortality, and Trends in Cardiovascular and Cerebrovascular Events Among Recreational Marijuana Users: A Five-year Nationwide Inpatient Assessment in the United States

Abstract: BackgroundRecent trends in the legalization of marijuana in many states are increasing the popularity of recreational marijuana use. Since current data on hospitalizations in marijuana users is sparse, we evaluated the primary reasons for admissions, procedures and associated healthcare burden in hospitalized recreational marijuana users.MethodsThe National Inpatient Sample (NIS) for the years 2010–2014 was queried for the hospitalizations with a history of recreational marijuana usage using applicable ICD-9 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
(31 reference statements)
1
23
0
Order By: Relevance
“…Studies suggest a high burden (15-20%) of substance abuse among adults with DKA-related hospitalizations [16-17]. Rising trends in drug abuse especially cocaine and marijuana have been concerning as these substances have the potential to increase the odds of MI, arrhythmia, and stroke as noted in prior studies [18-21]. Such practices make these patients prone towards discontinuation of insulin therapy, dietary transgressions, behavioral issues, stress and could alter metabolism leading to an increased risk of decompensation [8, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest a high burden (15-20%) of substance abuse among adults with DKA-related hospitalizations [16-17]. Rising trends in drug abuse especially cocaine and marijuana have been concerning as these substances have the potential to increase the odds of MI, arrhythmia, and stroke as noted in prior studies [18-21]. Such practices make these patients prone towards discontinuation of insulin therapy, dietary transgressions, behavioral issues, stress and could alter metabolism leading to an increased risk of decompensation [8, 16].…”
Section: Discussionmentioning
confidence: 99%
“…We identified ≥18 years IBD (both CD and UC) patients using ICD-9 CM codes 555.x (CD or regional enteritis) 556.x (UC). Among these patients, cannabis use was identified using ICD-9 CM codes 304.30, 304.31, 304.32, 305.20, 305.21, and 305.22 also used in our previous studies (5)(6)(7). We recognized associated in-hospital complications from the secondary discharge diagnoses/procedures.…”
Section: Study Populationmentioning
confidence: 99%
“…Nevertheless, we acknowledge that through combining and triangulating results of different methodological approaches, stronger claims toward causality may be supported. 3 The report of Amraotkar et al highlights the need to replicate our findings in other settings and through various study designs.…”
Section: Comments Adding a Us Perspective For Stroke Risk In Noncomplmentioning
confidence: 74%
“…PAD-related admissions, comorbidities, and stroke events in hospitalized older adult (≥65 years) patients were identified using International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes, as detailed in our earlier studies. [2][3][4] Medication noncompliance was identified using ICD-9 code V15.81, as previously validated. 5 Our analysis of 2014 nationwide US hospitalized patients (N = 337 800) showed that older adult noncompliant PAD patients with coexistent diabetes and dyslipidemia were frequently males, African Americans, and Hispanics, and from a lower quartile median household income (Table 1).…”
Section: Comments Adding a Us Perspective For Stroke Risk In Noncomplmentioning
confidence: 99%